Evaluating Properties of Asphalt Mixtures Containing polymers of Styrene Butadiene Rubber (SBR) and recycled Polyethylene Terephthalate (rPET) against Failures Caused by Rutting, Moisture and Fatigue - Mahmoud Ameri; Reza Mohammadi; Milad Mousavinezhad; Amirhossein Ameri; Hamid Shaker; Arash Fasihpour (Fracture and Structural Integrity)
Properties of asphalt mixture play a vital role in structural integrity and performance of flexible pavements structure. In flexible pavements, asphalt concrete surface layer consists of asphalt binder, aggregates and in some cases additives. In this research study styrene butadiene rubber (SBR) and recycled polyethylene terephthalate (rPET) are used to evaluate their individual and also their combinational effects on moisture susceptibly, rutting and low temperature cracking of asphalt concrete mixture. Combinations of SBR, rPET and water were vulcanized to form thermoplastic elastomer polymers as bitumen modifier. Then conventional bitumen tests including penetration grade, softening point and rotational viscosity (RV) as well as asphalt mixture tests including resilient modulus, dynamic creep, IDT fatigue and moisture susceptibility tests were performed on binders and asphalt mixture specimens. The test results indicated that SBR and rPET increase viscosity and softening point and stiffen the binders by reducing their penetration grade. Test results of specimens prepared with modified binders showed higher tensile strength and higher rutting resistance than that of control specimen. Within the content of this study it is concluded that modification of bitumen with SBR reduces low temperature stiffness of binder and hence reduces failure due to thermal cracking and modification with rPET increases rutting resistance of the mixture at high temperatures.